Combating Transnational Drug Trafficking: A Focus on Pakistan's Challenges and Countermeasures - Khan, Fahad Hameed; Shahzadi, Asma; Batool, Fatima (2025)
For decades, scholars have grappled with precisely defining Transnational Organized Crime (TOC). Reuter and Rubinstein cautioned back in the 1970s that pinpointing TOC would inevitably be the weak point in any investigation into cross-border illicit conduct. TOC involves numerous activities from drug and human trafficking to money laundering, insider trading, and corruption and spans across different actors, including agent provocateurs, operating in multiple countries. While recent laws have been enacted to criminalize these various acts, the sheer breadth of TOC makes it an exceptionally challenging subject to address. TOC generates between $1.6 to $2.2 trillion per year. and thus considered as a danger to international security due to its" explosive and destabilizing repercussions" potential. TOC poses a significant threat to both direct and indirect peace, as well as cultural peace. It jeopardizes human rights, world peace, and the Sustainable Development Goals (SDG). Academics and researchers are unable to convey knowledge about TOC because it is covert and hidden, and because it is related to elites. The industry of transnational organized crime especially drug trafficking; the largest facet of TOC (occupies 30-35% of Transnational Criminal activities) is one that is always adapting to new markets and developing new types. It is an illicit enterprise that cuts across all boundaries; cultural, social, linguistic, and geographic. This corporation does not recognize any borders or standards because it operates outside of them. This article explores the multifaceted ramifications of this illicit trade on Pakistan's internal socio-economic and political fabric, and how these vulnerabilities are, in turn, reflected in and contribute to a detrimental international image. Drawing on a comprehensive review of existing literature and reports, researchers argue that drug trafficking extends far beyond a mere law enforcement issue, deeply eroding governance, fueling corruption, and exacerbating internal security threats.